2019
DOI: 10.4269/ajtmh.19-0161
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Infectious Diarrhea Hot spots and Associated Socioeconomic Factors in Anhui Province, China

Abstract: Infectious diarrhea cases have increased during the past years in the Anhui Province of China, but little is known about its spatial cluster pattern and associated socioeconomic factors. We obtained county-level total cases of infectious diarrhea in 105 counties of Anhui in 2016 and computed age-adjusted rates. Socioeconomic factors were collected from the Statistical Yearbook. Hot spot analysis was used to identify hot and cold spot counties for infectious diarrhea incidence. We then applied binary logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In previous studies, diarrhea was found presenting a specific temporal and spatial distribution which usually clustered spatially in different geographical locations (25)(26)(27). Several factors including sociodemographic variables, personal hygiene, and environmental and climatic changing were considered to be associated with the incidence of diarrhea (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, diarrhea was found presenting a specific temporal and spatial distribution which usually clustered spatially in different geographical locations (25)(26)(27). Several factors including sociodemographic variables, personal hygiene, and environmental and climatic changing were considered to be associated with the incidence of diarrhea (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bandyopadhyay et al (5) found a decrease in monthly rainfall and increase in temperature during the dry season was able to delineate hotspots of diarrhea prevalence in children under the age of 3 years in sub-Saharan Africa. In Anhui Province of China, Hao et al (17) found a strong association between socio-economic status and spatial clustering of diarrhea incidence. These studies demonstrate that the combination of meteorological and socio-demographic factors create different suitable pathways for diarrhea transmission, which are likely to be setting-specific.…”
Section: Introductionmentioning
confidence: 99%
“…The densely populated areas, like urban areas, with lots of waterlogging and the flow of urbanization continuing to increase annually, have made the problem of population density the main scourge for various diseases as well as diarrhea (Jarquin et al, 2016). Research in Anhui China illustrates that densely populated areas have a higher burden of infectious diseases, including diarrhea, than less densely populated areas (Hao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are still people who still do not have easy access to healthcare facilities. It is affected by economic conditions related to geographical location Hao et al, 2019). The people having access to healthcare facilities are constrained by long distances and significant costs so that they cannot take advantage of these health facilities (Arvelo et al, 2019;Woldeamanuel, 2020).…”
Section: Resultsmentioning
confidence: 99%